Biosurfactant-sophorolipid acts in synergy with antibiotics to enhance their efficiency - Joshi-Navare, Kasturi; Prabhune, Asmita (Biomed Research International, 2013)
Sophorolipids (SLs), biosurfactants with antimicrobial properties, have been tried to address the problem of antibiotic resistance. The synergistic action of SL and antibiotics was checked using standard microdilution and spread plate methods. With Staphylococcus aureus, SL-tetracycline combination achieved total inhibition before 4 h of exposure while tetracycline alone couldnot achieve total inhibition till the end of 6 h. The inhibition caused by exposure of bacterium to SL-tetracycline mixture was similar to 25% more as compared to SL alone. In spite of known robustness of gram-negative bacteria, SL-cefaclor mixture proved to be efficient against Escherichia coli which showed similar to 48% more inhibition within 2 h of exposure as compared to cefaclor alone. Scanning electron microscopy of the cells treated with mixture revealed bacterial cell membrane damage and pore formation. Moreover, SLs being a type of asymmetric bola, they are expected to form self-assemblies with unique functionality. This led to the speculation that SLs being amphiphilic in nature can span through the structurally alike cell membrane and facilitate the entry of drug molecules.